Fast-response ionization-based flexible pressure sensor based on zinc ion mobility regulation
By introducing ion gel dielectric layers to introduce oxygen concentration (urea-urinary alkane) and silver nano wires, and introduce the hemorne-shaped groove structure on the surface, it solves the problem of poor ability to respond under high-frequency pressure and realize it. The rapid response and high -frequency capture capabilities are improved.
Patent Information
- Application Number
- CN202411562330.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Existing ionized flexible pressure sensors have poor response capabilities under fast signal changes and cannot effectively capture high-frequency pressure information. This is mainly due to the hindered migration of ions in the ion gel dielectric layer, resulting in a long transmission path and a slow migration speed.
Using technology based on zinc ion mobility regulation, a fast ion transmission channel is constructed by introducing oxygen-rich poly(urea-urethane) and silver nanowires into the ion gel dielectric layer, and semi-ellipsoids are introduced on the surface of the dielectric layer. Spherical groove structure to increase contact area.
It significantly improves the migration speed and efficiency of zinc ions, enabling the sensor to quickly respond to high -frequency pressure signals, and enhances the ability to capture high -frequency pressure information.
Smart Images

Figure CN119063885B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sensors, and in particular relates to a fast-response ionization-type flexible pressure sensor based on zinc ion mobility regulation. Background Art
[0002] Flexible capacitive pressure sensors have attracted much attention in the fields of robot touch, human-computer interaction, smart wearable devices and the metaverse due to their high sensitivity, high flexibility and low power consumption. As a dielectric layer, the ion gel membrane has good ionic conductivity, and combined with the double layer theory, it can realize an ultra-high sensitivity ion-type pressure sensor. However, due to the influence of the solvation sheath or the viscosity of the ions inside the dielectric layer, they cannot quickly migrate to the surface of the dielectric layer to form a double layer structure, which greatly affects the response ability of the ion-type flexible pressure sensor under rapid signal changes.
[0003] Patent application CN112911994A proposes a wearable footwear sensor array for detecting cardiovascular pulse physiological activities, body movements and muscle actions, which utilizes the array orientation around the dorsalis pedis and the high performance characteristics of a single sensor, including high flexibility, high sensitivity, fast response time and a wide sensing range of shoes and cardiovascular pulse pressure.
[0004] Patent application CN116421146A proposes a flexible electronic skin system and a method for preparing a flexible sensor thereof, and prepares a fully solid-state ion selective sensor to improve the flexible sensor's ability to perceive weak pressures, and can measure weak dynamic signals of the human body such as pulse, Adam's apple vibration, etc.
[0005] Patent application CN114184308A proposes an integrated fully flexible ionization sensor based on laser engraving and a preparation method thereof, which realizes the integrated assembly of the flexible ionization sensor by introducing ionic liquid into thermoplastic polyurethane to achieve a low response time.
[0006] Patent application CN115342950A uses the coordination of a zinc oxide nanowire network structure layer and a carbon structure layer to utilize strain-induced generation of charged small molecules in the zinc oxide nanowires to increase the mobility of carriers in the carbon structure layer, thereby improving the sensitivity and response speed of the sensor.
[0007] In the academic paper "Strong and Tough Physical Eutectogels Regulated by the Spatiotemporal Expression of Non-Covalent Interactions" published in the journal Advanced Functional Materials, Zhang's team proposed a simple and general solvent replacement method to regulate the spatiotemporal expression of intra-polymer / inter-polymer interactions to prepare strong physical eutectic glues, which are expected to be used in the dielectric layer of ionized pressure sensors to improve the frequency response characteristics of the sensors.
[0008] In the academic paper "Peptide-enhanced tough, resilient and adhesive eutectogels for highly reliable strain / pressure sensing under extreme conditions" published in the journal Nature Communications, Zhang's team synthesized peptide-enhanced eutectic gels by introducing the α-helical "molecular spring" structure into deep eutectic solvents, achieving high tensile / compression, good resilience, excellent fracture toughness, excellent fatigue resistance and strong adhesion, which can enable ion-type sensors to effectively rebound after being stressed, thereby improving the sensor response speed.
[0009] In the academic paper "Gradual Electrical-Double-Layer Modulation in Ion-Polymer Networks for Flexible Pressure Sensors with Wide Dynamic Range" published in the journal Advanced Functional Materials, Lee's team proposed a planar, textureless dielectric layer based on an ionic polymer network. The pressure-induced ion penetration into the porous polymer network leads to the gradual formation of EDL, which can achieve high sensitivity and a wide dynamic range.
[0010] Zhang's team published an academic paper titled "Ultrafast piezocapacitive soft pressure sensors with over 10 kHz bandwidth via bonded microstructured interfaces" in the journal Nature Communications. The paper achieved ultrafast response of the sensor by using doped carbon nanotubes to reduce viscosity and combining bonded microstructured interfaces to reduce interface friction energy dissipation.
[0011] In summary, relevant researchers have carried out a lot of research work on the fast response characteristics of ionization pressure sensors, but there are still the following shortcomings:
[0012] 1. Ionic gels usually use ionic liquids to provide double-layer capacitance charges. However, most ionic liquids have high viscosity during application, and their large molecular weight makes it easier to form a solvation sheath around them, which hinders their rapid migration in the gel and affects the response time of the sensor.
[0013] 2. Ion-type pressure sensors sense pressure changes through the double-layer capacitance constructed between the electrode and the dielectric layer. However, due to the complexity of the internal network structure of traditional ion gels, it is difficult to form an efficient and fast ion transmission channel. This causes ions to be hindered during the transmission process and cannot quickly reach the surface of the dielectric layer, thereby prolonging the response time of the sensor and causing the sensor to be unable to capture high-frequency pressure information.
[0014] 3. The contact area between the electrode and the dielectric layer of the ion-type pressure sensor is limited. The double-layer capacitance can only be generated on the surface of the dielectric layer. The ion migration path is long and the double-layer capacitance cannot be formed in time. Currently, few studies have taken into account the design of the body structure that introduces electrons into the dielectric layer through the electrode. When processing high-frequency signals, the sensor cannot respond quickly due to the long ion migration path.
[0015] 4. Ion-type pressure sensors often introduce microstructures on the surface of the dielectric layer to achieve ultra-high sensitivity by modulating the contact area between the microstructure and the electrode. Although the contact area modulation of the structure surface can achieve ultra-high sensitivity by changing the double-layer capacitance, the stress is mostly concentrated on the top of the independent microstructure during the modulation process. Under high-frequency vibration, the microstructure is difficult to rebound in time, which greatly limits the high-frequency response of the ion-type pressure sensor.
[0016] 5. During the contact area modulation process, the dielectric layer and the electrode of the ion-type pressure sensor are in contact and separation, resulting in energy dissipation. The lack of effective adhesive between the electrode and the dielectric layer makes it easy for the sensor electrode and the dielectric layer to loosen or fall off, resulting in incomplete rebound of the dielectric layer, slow dynamic response of the sensor, and inability to respond quickly to high-frequency pressure information.
[0017] 6. Ion-type pressure sensors have a low linear range, and usually introduce microstructures in the dielectric layer to optimize the linear relationship between the sensor's input and output. However, the lower capacitor (the capacitor formed between the lower electrode and the dielectric layer) is connected in series with the upper capacitor (the capacitor between the upper electrode and the dielectric layer) in the sensor circuit, and the presence of the lower capacitor leads to a decrease in high-frequency sensitivity under pre-stressing. Summary of the invention
[0018] In view of the shortcomings of the prior art, the present invention proposes a fast-response ionization flexible pressure sensor based on zinc ion mobility regulation, which effectively improves the response characteristics of such flexible pressure sensors under high-frequency pressure.
[0019] To achieve the purpose, the present invention adopts the following technical solution:
[0020] The invention discloses a fast-response ion-type flexible pressure sensor based on zinc ion mobility regulation, which is characterized in that: the ion-type flexible pressure sensor has an ion gel dielectric layer as a central layer, a flexible electrode layer is fixed on the upper surface of the ion gel dielectric layer by an adhesive layer, and an interlocking electrode layer is arranged on the lower surface.
[0021] Furthermore, the interlocking electrode layer is made of conductive mesh and embedded in the lower surface of the ion gel dielectric layer, thereby forming a topological interlocking structure with the ion gel dielectric layer.
[0022] Furthermore, the ion gel dielectric layer is a gel film, and the upper surface of the film is uniformly distributed with semi-ellipsoidal grooves. The semi-ellipsoidal grooves whose long axes are parallel to the length direction of the ion gel dielectric layer are transverse grooves, and the semi-ellipsoidal grooves whose long axes are parallel to the width direction of the ion gel dielectric layer are longitudinal grooves, and the transverse grooves and the longitudinal grooves are arranged at intervals along the length direction and the width direction of the ion gel dielectric layer, respectively. Furthermore, the spacing between adjacent semi-ellipsoidal grooves does not exceed 7 μm, and the long axis chord length of each ellipsoidal groove does not exceed 12 μm, and the short axis chord length does not exceed 8 μm.
[0023] Furthermore, the total thickness of the ion gel dielectric layer is 150-350 μm, the ultimate stress is 15-20 MPa, and the toughness is not less than 60 MJ / m 3 , tearing energy not less than 40 MJ / m 2 .
[0024] Furthermore, the preparation method of the ion gel dielectric layer is: dissolving acrylamide (AM) and oxygen-rich poly (urea-urethane) (OR-PUU) in deionized water, adding an active agent, heating and stirring until the whole is in a uniformly mixed viscous state, and then vacuum degassing to obtain a flexible ion gel material; casting the flexible ion gel material into a mold, and immersing the mold in a deep eutectic solvent for solidification, after taking it out, embedding the conductive mesh into the lower surface of the ion gel dielectric layer by hot pressing, and then drying and demolding to form an ion gel dielectric layer containing an interlocking electrode layer.
[0025] Furthermore, in the flexible ion gel material, the mass ratio of acrylamide (AM) to oxygen-enriched poly(urea-urethane) (OR-PUU) is 7-15:1; the active agent is ammonium persulfate, and the amount of the active agent added is 2-3.5% of the mass of acrylamide.
[0026] Furthermore, the deep eutectic solvent is prepared by heating and stirring ZnCl2, silver nanowires (AgNWs), choline chloride (ChCl), and urea in ethylene glycol (EG) at 110-140°C, and the molar ratio of each raw material is: ChCl 7.5-12.5%, urea 25-30%, AgNWs 0.5-1.5%, ZnCl25-10%, and the balance is EG.
[0027] Furthermore, the preparation method of the adhesive layer is as follows: (1) adding 2-(4-aminophenyl-4-[4-(4-aminophenoxy)phenyl]-2,3-naphthyridin-1-one (DHPZDA), 4,4'-diaminodiphenyl ether (ODA), and 1,3-bis(4-aminophenoxy)benzene (TPER) to NMP solvent, stirring under a nitrogen environment at 220-230° C. until the raw materials are completely dissolved, cooling to room temperature, and then adding 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), bisphenol A diether dianhydride (BPADA) and 4,4'-oxydiphthalic anhydride (ODPA) at room temperature, stirring until the whole is in a uniformly mixed viscous state, thereby obtaining a PAA adhesive; the composition of the raw materials in the PAA adhesive by mass percentage is: DHPZDA 6.5-7%, ODA 12.5-13.5%, TPER 22-24%, BPDA 22~24%, BPADA 24~26%, ODPA 9.5~10.5%. (2) Printing PAA adhesive on the surface of the flexible electrode layer to form an adhesive layer; and then fixing the flexible electrode layer on the upper surface of the ion gel dielectric layer through the adhesive layer.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0029] 1. The present invention selects Zn 2+As the charged electron in the double layer capacitor structure, Zn 2+ Compared with monovalent ionic liquids, ions have a smaller ionic radius, which will reduce the solvated molecules formed around the charged electrons, and have a smaller migration resistance than ionic liquids. In addition, higher charge can be affected by a larger electric field force, and can quickly migrate to the surface of the dielectric layer to form a double electric layer structure.
[0030] 2. The present invention introduces oxygen-rich poly(urea-urethane) (OR-PUU) into polyacrylamide-based gel, and uses the ion hopping migration mechanism to construct ion transport channels. The long-chain OR-PUU molecules construct a fast Zn 2+ Ion transport channel. Oxygen-rich poly (urea-urethane) is a specially designed polymer that introduces additional oxygen atoms through molecular engineering. The carbonyl group (C=O) rich in oxygen has a high electronegativity and can serve as an active site for ion migration, promoting Zn 2+ adsorption and migration, effectively improving Zn 2+ The migration speed in the ion gel enables the sensor to respond promptly to rapidly changing pressure signals.
[0031] 3. The present invention introduces silver nanowires (AgNWs) into the ion gel dielectric layer. AgNWs generate positive and negative charges under the action of the electric field, forming an in-body microstructure and forming a double-layer capacitor inside the dielectric layer, shortening the transmission path of ions in the dielectric layer, improving migration efficiency, and reducing migration time. At the same time, the introduction of AgNWs reduces the adhesion of the ion gel to reduce energy dissipation during the area modulation process, ensuring rapid dynamic response of the sensor.
[0032] 4. The ternary deep eutectic solvents (DESs) used in the present invention can provide abundant dynamic interaction sites, such as hydrogen bonds and ion-dipole interactions, due to the interactions between the components, which helps to improve the mobility of ions and the conductivity of electrolytes. Due to their low freezing point and high boiling point, ternary DESs can be used under extreme climatic conditions, including low and high temperature environments, which improves the practicality and stability of sensors. The present invention uses ternary DESs to replace water to enhance the expression of polymer-polymer interactions and promote the formation of uniformly distributed small-sized crystals as cross-linking points in the OR-PUU / PAM network, thereby completing the "network reconstruction". Driven by the spatiotemporal expression of polymer interactions in water and DESs, a stable physical cross-linking network can be established, and the resulting OR-PUU / PAM eutectic gel has excellent deformability and high strength, allowing the dielectric layer to rebound quickly during contact area modulation.
[0033] 5. The present invention adopts a casting process and a mold forming method to introduce an integrated recessed microstructure on the surface of the ion gel dielectric layer. The structural feature of the ellipsoidal groove is that its slope slows down as the depth of the depression increases. By introducing a surface structure with an elliptical groove, the contact area between the dielectric layer and the electrode is increased at the same downward pressure depth, thereby improving the sensitivity of the sensor and ensuring the linearity of the sensor. In addition, the integrated recessed microstructure can disperse the force on the top of the microstructure. Compared with an independent recessed microstructure, it has a higher pressure sensing range and smaller elastic hysteresis. It ensures the rebound of the microstructure during the area modulation process, so that the sensor has both a wide working range and high frequency characteristics. The transverse grooves and the longitudinal grooves are arranged at intervals, and the shear force is evenly dispersed while ensuring that the mechanical properties of the sensor are the same in the transverse and longitudinal directions.
[0034] 6. The present invention sets a PAA adhesive layer between the ion gel dielectric layer and the electrode. The flexible groups (such as ether bonds and isopropyl groups) introduced into the PAA adhesive increase the flexibility of the molecular chain, making it easier for the molecular chain to spread and infiltrate the electrode surface, thereby improving the physical adhesion between the adhesive and the electrode; in addition, the nitrogen atoms in the PAA adhesive molecular chain can form coordination bonds with the metal elements on the electrode surface. This chemical bonding enhances the adhesion between the adhesive and the metal. Therefore, the ion gel dielectric layer and the electrode have good interfacial adhesion, which improves the stability of the sensor.
[0035] 7. The present invention uses a hot pressing process to ensure that the dielectric layer fully covers the conductive mesh of the lower electrode, thereby realizing a topological interlocking structure between the dielectric layer and the lower electrode. This structure elevates the contact interface from the traditional two-dimensional plane to a three-dimensional space, increases the attachment area between the two, increases the double-layer capacitance between the ion gel dielectric layer and the lower electrode, improves linearity, and ensures high sensitivity under high-frequency pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is the overall structural diagram of the fast-response ionization flexible pressure sensor based on zinc ion mobility regulation of the present invention.
[0037] Figure 2 Schematic diagram of the arrangement of transverse grooves and longitudinal grooves on the surface of the ion gel dielectric layer.
[0038] Figure 3 Schematic diagram of the network structure of the gel during the evolution from sol to gel in the preparation of the ion gel dielectric layer.
[0039] Figure 4 Schematic diagram of the modulus and toughness of eutectic ion gels made from AM aqueous solutions with different mass fractions.
[0040] Figure 5Schematic diagram of the interlocking of the ion gel dielectric layer and the interlocking electrode layer.
[0041] Figure 6 This is the stress-capacitance change rate curve of the ion-type flexible pressure sensor prepared in Example 1 under a stress range of 200 kPa.
[0042] Figure 7 This is the normalized change curve of capacitance of the ion-type flexible pressure sensor prepared in Example 1 during the pressure loading-unloading process of 0~50kPa.
[0043] Figure 8 This is a schematic curve of the response time and recovery time of the ion-type flexible pressure sensor prepared in Example 1 under a stress change of 50 kPa.
[0044] Fig. 9 This is the vibration response characteristic curve of the ion-type flexible pressure sensor prepared in Example 1 to different frequencies under pre-pressure (~50 kPa).
[0045] Fig.10 This is a spectrum diagram of the ion-type flexible pressure sensor prepared in Example 1 detecting 995 Hz, 1000 Hz, 1005 Hz and 1010 Hz signals.
[0046] Fig.11 This is the repetitive characteristic curve of the ion-type flexible pressure sensor prepared in Example 1. DETAILED DESCRIPTION
[0047] The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.
[0048] Acrylamide used in the following examples was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (AR, 99.0%).
[0049] The oxygen-enriched poly(urea-urethane) (OR-PUU) used in the following examples was prepared according to the method described in the literature "Molecular Engineering Enables Hydrogel Electrolyte with Ionic Hopping Migration and Self-Healability toward Dendrite-Free Zinc-Metal Anodes" (ZHU K, LUO J, ZHANG D, et al. 2024. Molecular Engineering Enables Hydrogel Electrolyte with Ionic Hopping Migration and Self-Healability toward Dendrite-Free Zinc-Metal Anodes [J / OL]. Advanced Materials, 36 (19): 2311082.). The sources of the raw materials involved in the synthesis are as follows: SDS was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (AR, 92.5-100.5%). DTBU was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (99.0%). IDA was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (cis-trans mixture, 99.0%). Hexadecane was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (>99.5%, GC). Poly(propylene glycol), tolyl-2,4-diisocyanate terminated (PPGTD) was purchased from Shanghai MacLean Biochemical Technology.
[0050] The ammonium persulfate used in the following examples was purchased from China National Pharmaceutical Group Chemical Reagent Co., Ltd. (chemically pure, CP).
[0051] Choline chloride used in the following examples was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (AR, 98.0%).
[0052] The urea used in the following examples was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (AR, 99.0%).
[0053] The ethylene glycol used in the following examples was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (AR, 98.0%).
[0054] The DHPZDA used in the following examples was prepared according to the method described in the document “Synthesis and Performance Study of Copolyimide Containing Naphthalene Biphenyl Structure” (Su Guixian. Synthesis and Performance Study of Copolyimide Containing Naphthalene Biphenyl Structure [D]. Dalian University of Technology, 2010.).
[0055] The ODA used in the following examples was purchased from Shanghai Kefeng Industrial Co., Ltd. (chemically pure, CP).
[0056] The TPER used in the following examples was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (98.0%, HPLC).
[0057] The ODPA used in the following examples was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (97.0%).
[0058] BPADA used in the following examples was purchased from Shanghai BiDe Pharmaceutical Technology Co., Ltd. (97.0%).
[0059] The BPDA used in the following examples was purchased from Beijing Bailingwei Technology Co., Ltd. (99.0%).
[0060] The NMP used in the following examples was purchased from Tianjin Kemeiou Chemical Reagent Co., Ltd. (analytical grade, AR).
[0061] Example 1
[0062] like Figure 1 As shown, the fast-response ion-type flexible pressure sensor based on zinc ion mobility regulation provided in this embodiment is a sandwich-like structure as a whole, with an ion gel dielectric layer 1 as the central layer, an adhesive layer 2 and a flexible electrode layer 3 are arranged on the upper surface of the ion gel dielectric layer, and an interlocking electrode layer 4 is arranged on the lower surface.
[0063] The fast-response ionization-type flexible pressure sensor based on zinc ion mobility regulation of this embodiment is manufactured according to the following steps:
[0064] Step 1: Preparation of an ion gel dielectric layer containing an interlocking electrode layer
[0065] 500 g of choline chloride, 500 g of urea and 1400 mL of ethylene glycol were mixed and magnetically stirred at a high temperature of 140 °C until the solvent was uniform and transparent. 400 g of ZnCl2 and 50 g of AgNWs were added and continued to heat and stir until the AgNWs were evenly dispersed to obtain a deep eutectic solvent containing electrolyte.
[0066] 30 g acrylamide and 4 g OR-PUU were added to 150 mL deionized water and vigorously mechanically stirred for 3 h. Subsequently, 0.6 g ammonium persulfate was added to the mixture solution and stirred continuously at 80 °C for 10 min. The whole solution showed a uniformly mixed viscous state. After vacuum degassing for 30 min, a flexible ion gel material was obtained.
[0067] Use modeling software to draw the mold for making the ion gel dielectric layer. Cast the flexible ion gel material into the mold, and soak the mold in 200 mL of deep eutectic solvent for curing for 5 hours. During this period, the deep eutectic solvent is replaced every 1 hour to ensure that the moisture is replaced by the deep eutectic solvent. After the infiltration is completed, take out the mold, take a piece of 1.5cm×0.5cm×0.1mm conductive mesh, move the conductive mesh with an area of 1cm×0.5cm to the lower surface of the ion gel dielectric layer, and pressurize 100kPa at 80°C to embed the conductive mesh into the ion gel dielectric layer, and reserve 0.5cm×0.5cm of the conductive mesh as the lead-out wire. Subsequently, move it to a constant temperature box at 70°C for drying and curing for 4 hours, demold it, and form an ion gel dielectric layer containing an interlocking electrode layer. The total thickness of the ion gel dielectric layer obtained in this embodiment is 200μm, the ultimate stress is 20MPa, and the toughness is 60 MJ / cm 3 , tearing energy is 40MJ / cm 2 The upper surface of the obtained ion gel dielectric layer is uniformly distributed with semi-ellipsoidal grooves. Figure 2 As shown, the semi-ellipsoidal grooves whose long axis is parallel to the length direction of the ion gel dielectric layer are lateral grooves, and the semi-ellipsoidal grooves whose long axis is parallel to the width direction of the ion gel dielectric layer are longitudinal grooves, and the lateral grooves and the longitudinal grooves are arranged at intervals along the length direction and the width direction of the ion gel dielectric layer, respectively. The spacing between adjacent semi-ellipsoidal grooves is 4 μm, and the long axis chord length of each ellipsoidal groove is 9 μm and the short axis chord length is 6 μm.
[0068] Step 2: Prepare the bonding layer
[0069] 0.4g DHPZDA, 0.8g ODA and 1.4g TPER were added to 20mL NMP solvent and mechanically stirred in a dry container with nitrogen at 220°C. After the above raw materials were completely dissolved, they were cooled to room temperature, and then 1.4g BPDA, 1.5g BPADA and 0.6g ODPA were added at room temperature, and stirring continued under nitrogen environment. After 12 hours of reaction, a viscous PAA adhesive was obtained. The PAA adhesive was evenly scraped on the surface of the copper foil using a screen printing process, and placed on a hot plate at 60°C to dry for 2h. Then it was attached to the upper surface of the ion gel dielectric layer, and 10kPa was applied at 80°C to ensure that the PAA adhesive tightly adhered to the copper foil electrode and the ion gel dielectric layer. The thickness of the bonding layer obtained in this embodiment is 4μm. After testing, the dielectric constant of the bonding layer is 3.1, the dielectric loss is as low as 0.003, and the peel strength is 0.83N / mm.
[0070] Figure 3The figure is a schematic diagram of the network structure of the gel during the evolution from sol to gel in the preparation of the ion gel dielectric layer. The present invention adopts solvent replacement technology to prepare the ion gel, first dissolving PAM / OR-PUU with deionized water, and then replacing the deionized water with DESs. If DESs are directly used for heating and dissolution, although the interaction between polymers can be destroyed and the "polymer dissociation" of PAM / OR-PUU can be achieved, the subsequent cooling process cannot restore the broken network connection, that is, the required "network reconstruction" will not occur in the PAM / OR-PUU gel dissolved by DESs. The present invention uses solvent replacement technology to easily and effectively regulate the spatiotemporal expression of polymer interactions, so that PAM / OR-PUU "dissociates" in water, weakens the interaction of polymers according to thinking, and can also timely enhance the interaction of polymers, inducing the formation of uniformly distributed small-sized PAM / OR-PUU crystals, thereby rebuilding a uniform and robust polymer network.
[0071] In the preparation of the above-mentioned ion gel dielectric layer, in order to compare the effect of the amount of acrylamide on the mechanical properties of the gel, the amount of deionized water was adjusted so that the mass percentage of acrylamide in deionized water was 18%, 20%, 22%, and 24%, respectively. Then, the flexible ion gel material was prepared according to the same method as above and formed into an ion gel dielectric layer (without conductive mesh), and a mechanical tensile test was performed on it using a tensile press ZQ990B. Figure 4 Schematic diagram of the modulus and toughness of eutectic ion gels made from different mass fractions of AM aqueous solutions. It can be seen that with the increase in the mass percentage of PAM, the toughness and modulus of the gel increase, but the increase trend gradually slows down. However, the ion mobility of the eutectic ion gel decreases with the increase in the mass percentage of PAM, so choosing 20%~22% PAM can maintain a higher Young's modulus, toughness and ion mobility.
[0072] Figure 5 The diagram shows the interlocking of the ion gel dielectric layer and the interlocking electrode layer. The dielectric layer is ensured to fully cover the conductive mesh of the lower electrode, thereby realizing the topological interlocking structure between the dielectric layer and the lower electrode. This structure elevates the contact interface from the traditional two-dimensional plane to a three-dimensional space, increases the attachment area between the two, increases the double-layer capacitance between the ion gel dielectric layer and the lower electrode, improves linearity, and ensures high sensitivity under high-frequency pressure.
[0073] Figure 6The stress-capacitance change rate curve of the ion-type flexible pressure sensor prepared in this example under the stress range of 200kPa. The obtained sensor was fixed on the measurement platform, and the stress of 0~200KPa was applied to the sensor by the tension press ZQ990B, and the sensor capacitance of the sensor was measured by TH2829. The results show that under the stress range of 0~100kPa, the sensor can still have a capacitance of 0.413kPa. -1 High sensitivity and high linearity of 0.985.
[0074] Figure 7 This is the normalized change curve of the capacitance of the ion-type flexible pressure sensor prepared in this embodiment during the pressure loading-unloading process of 0-50 kPa. It can be seen that during the loading-unloading process, the response hysteresis is very small, and there is almost no capacitance-pressure hysteresis loop. The low hysteresis is related to the negligible viscous dissipation of the interface.
[0075] In order to evaluate the dynamic response speed of the sensor, a 500 g weight (equivalent pressure ~50 kPa) was gently placed on the ionized flexible pressure sensor prepared in this example and then quickly released. Figure 8 The response time and recovery time of the sensor under a stress change of 50kPa are schematically shown in the figure. The results show that the response time and relaxation time are both 0.5ms.
[0076] Under the pre-pressure of 50 kPa, the ion-type flexible pressure sensor prepared in this embodiment is subjected to vibration detection at different frequencies. The response curve is as follows: Fig. 9 It can be seen that the sensor can effectively detect the superimposed static and vibration signals under the conditions of additionally applying vibration signals of 100Hz, 500Hz and 1000Hz.
[0077] Frequency resolution is an indicator that determines the performance of a sensor in resolving approximate frequencies. The ion-type flexible pressure sensor prepared in this embodiment is loaded with superimposed signals of 995 Hz, 1000 Hz, 1005 Hz and 1010 Hz. Fig.10 This is the spectrum diagram obtained by converting the data into frequency domain. It can be seen that the sensor can clearly distinguish the 5Hz vibration signal.
[0078] The ion-type flexible pressure sensor prepared in this embodiment was subjected to 5000 compression cycles, and the capacitance change was recorded. Fig.11 This is a repetitive characteristic curve. It can be seen from the curve that the sensor still has good repeatability even after multiple compressions.
[0079] The above description is only an exemplary embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A fast-response ionization flexible pressure sensor based on zinc ion mobility regulation, characterized in that: The ion gel dielectric layer is used as the central layer of the ion gel dielectric layer, a flexible electrode layer is fixed on the upper surface of the ion gel dielectric layer through an adhesive layer, and an interlocking electrode layer is arranged on the lower surface; The ion gel dielectric layer is a gel film, and the upper surface of the film is uniformly distributed with semi-ellipsoidal grooves; The interlocking electrode layer is made of conductive mesh and embedded in the lower surface of the ion gel dielectric layer, thereby forming a topological interlocking structure with the ion gel dielectric layer; The semi-ellipsoidal grooves whose long axes are parallel to the length direction of the ion gel dielectric layer are called transverse grooves, and the semi-ellipsoidal grooves whose long axes are parallel to the width direction of the ion gel dielectric layer are called longitudinal grooves. The transverse grooves and the longitudinal grooves are arranged at intervals along the length direction and the width direction of the ion gel dielectric layer, respectively.
2. The fast-response ionization flexible pressure sensor based on zinc ion mobility regulation according to claim 1, characterized in that: The spacing between adjacent semi-ellipsoidal grooves does not exceed 7 μm, the major axis chord length of each ellipsoidal groove does not exceed 12 μm, and the minor axis chord length does not exceed 8 μm.
3. The fast-response ionization flexible pressure sensor based on zinc ion mobility regulation according to claim 1, characterized in that: The total thickness of the ion gel dielectric layer is 150-350 μm, the ultimate stress is 15-20 MPa, and the toughness is not less than 60 MJ / m 3 , tearing energy not less than 40 MJ / m 2 .
4. The fast-response ionization flexible pressure sensor based on zinc ion mobility regulation according to claim 1, characterized in that: The preparation method of the ion gel dielectric layer is as follows: The acrylamide and oxygen-enriched poly(urea-urethane) are dissolved in deionized water, and an active agent is added and heated and stirred until the whole is in a uniformly mixed viscous state, and then vacuum degassing is performed to obtain a flexible ion gel material; The flexible ion gel material is cast into a mold, and the mold is immersed in a deep eutectic solvent for solidification. After being taken out, the conductive mesh is embedded into the lower surface of the ion gel dielectric layer by hot pressing, and then dried and demolded to form an ion gel dielectric layer containing an interlocking electrode layer.
5. The fast-response ionization flexible pressure sensor based on zinc ion mobility regulation according to claim 4, characterized in that: In the flexible ion gel material, the mass ratio of acrylamide to oxygen-enriched poly(urea-urethane) is 7-15:1; the active agent is ammonium persulfate, and the added amount of the active agent is 2-3.5% of the mass of acrylamide.
6. The fast-response ionization flexible pressure sensor based on zinc ion mobility regulation according to claim 4, characterized in that: The deep eutectic solvent is prepared by heating and stirring ZnCl2, silver nanowires, choline chloride and urea in ethylene glycol at 110-140°C, and the molar ratio of each raw material is: choline chloride 7.5-12.5%, urea 25-30%, silver nanowires 0.5-1.5%, ZnCl2 5-10%, and the balance is ethylene glycol.
7. The fast-response ionization flexible pressure sensor based on zinc ion mobility regulation according to claim 1, characterized in that: The preparation method of the bonding layer is: 2-(4-aminophenyl-4-[4-(4-aminophenoxy)phenyl]-2,3-naphthyrazine-1-one DHPZDA, 4,4'-diaminodiphenyl ether ODA, and 1,3-bis(4-aminophenoxy)benzene TPER are added to an NMP solvent, stirred under a nitrogen environment at 220-230° C. until the raw materials are completely dissolved, cooled to room temperature, and then 3,3',4,4'-biphenyltetracarboxylic dianhydride BPDA, bisphenol A type diether dianhydride BPADA, and 4,4'-oxydiphthalic anhydride ODPA are added at room temperature, stirred until the whole is in a uniformly mixed viscous state, to obtain a PAA adhesive; The PAA adhesive is printed on the surface of the flexible electrode layer to form a bonding layer; and then the flexible electrode layer is fixed on the upper surface of the ion gel dielectric layer through the bonding layer.
8. The fast-response ionization flexible pressure sensor based on zinc ion mobility regulation according to claim 7, characterized in that: The composition of the raw materials in the PAA adhesive by mass percentage is: DHPZDA 6.5-7%, ODA 12.5-13.5%, TPER 22-24%, BPDA 22-24%, BPADA 24-26%, and ODPA 9.5-10.5%.
Citation Information
Patent Citations
Wearable footwear sensor arrays for detection of cardiac events, body motion, and muscular actions
CN112911994A
Integrated full-flexible ionizing sensor based on laser engraving and preparation method of integrated full-flexible ionizing sensor
CN114184308A
Quick-response high-sensitivity flexible sensor and preparation method thereof
CN115342950A
Preparation method of hydrogel flexible strain sensor with resistance-capacitance dual modes and sensor
CN113787800A
Wide-stress full-linear flexible ionizing sensor and preparation method thereof
CN116593036A